2010
DOI: 10.1159/000323998
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin-A Induced Toxicity in Rat Renal Collecting Duct Cells: Interference with Enhanced Hypertonicity Induced Apoptosis

Abstract: Background/ Aims: Rat renal inner medullary collecting duct (IMCD) cells are physiologically exposed to a wide range of ambient tonicity. To maintain their function upon changes in osmolality, IMCD cells induce expression of osmoprotective and antiapoptotic genes, mainly mediated by the transcription factor Tonicity Enhancer Binding Protein (TonEBP). Some drugs like Cyclosporin-A (CsA) are discussed to interfere with the activity of TonEBP and thereby mediate their nephrotoxic effects. The aim of our study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…Here, we did not see any difference in TonEBP localization as well as TonEBP mediated transcription [40].…”
Section: Decrease Of Aqp2 By Csa Is Independent Of Calcineurincontrasting
confidence: 64%
See 1 more Smart Citation
“…Here, we did not see any difference in TonEBP localization as well as TonEBP mediated transcription [40].…”
Section: Decrease Of Aqp2 By Csa Is Independent Of Calcineurincontrasting
confidence: 64%
“…However, there are conflicting results concerning the effect of CsA on TonEBP activity and localization [40,41]. Very similar to these previous studies, we analyzed expression of characteristic target genes and the subcellular distribution of TonEBP to estimate its activation status by different osmolality compositions of the culture media (6 days cultivation, 300 and 600 mOsm/ kg, medium differing in supplemental urea and NaCl).…”
Section: Decrease Of Aqp2 By Csa Is Independent Of Calcineurinmentioning
confidence: 80%
“…It has long been known that CsA induces apoptosis of proximal tubule cells (9,33). A recent study (40) has shown that CsA also induces apoptosis of inner medullary collecting duct cells by elevating osmolality. However, it remains unclear whether CsA can induce apoptosis of cortical collecting duct (CCD) cells.…”
mentioning
confidence: 99%
“…Differences in the efficacy of CsA between TBI and SCI may be attributed to fundamental differences in spinal cord and cortical mitochondria (Sullivan et al, 2004a). Regardless of any positive results, however, CsA is highly toxic, making it less than ideal as a therapeutic (Caramelo et al, 2004;Schenk et al, 2010;Rabchevsky et al, 2011;Szalowska et al, 2015). NIM811 (N-methyl-4-isoleucine cyclosporin) is an analog of CsA that also inhibits the mPTP, is much less toxic, and lacks immunosuppressive properties (Waldmeier et al, 2002).…”
Section: Mitochondrial-based Treatmentmentioning
confidence: 99%